Infectious diseases and risk of leukemia and non-Hodgkin's lymphoma: a case-control study - Parodi, Stefano; Santi, Irene (Leukemia research, 2012)
The aim of this investigation was to evaluate the association between common infectious diseases and the risk of hematological malignancies in an adult population. Data were drawn from a population based case-control study that included 165 cases (125 lymphoid and 40 myeloid neoplasms) and 233 controls. Occurrence of childhood diseases (measles, rubella, chickenpox, mumps, pertussis and scarlet fever) was slightly inversely associated with the risk of both malignancies, but statistical significance was not reached. The data of infections occurring after 14 years of age indicated an increasing risk of lymphoid malignancies (OR=2.9, p<0.05).